Pulmonary Function and Long-Term Respiratory Symptoms in Children and Adolescents After COVID-19 - Knoke, Leona; Schlegtendal, Anne; Maier, Christoph; Eitner, Lynn; Lücke, Thomas; Brinkmann, Folke (Frontiers in Pediatrics, 2022)
Background: Persistent respiratory symptoms after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in adults are frequent, and there can be long-term impairment of pulmonary function. To date, only preliminary evidence is available on persistent respiratory sequelae of SARS-CoV-2 in children and adolescents. Our objective was to examine the long-term effects of symptomatic and asymptomatic SARS-CoV-2 infections on pulmonary function in this age group in a single-center, controlled, prospective study. Methods: Participants with serological or polymerase chain reaction-based evidence of SARS-CoV-2 infection were recruited from a population-based study of seroconversion rates. Multiple-breath washout (MBW), body plethysmography, and diffusion capacity testing were performed for children and adolescents. Participants were interviewed about their symptoms during the acute phase of infection and long-lasting symptoms. Cases were compared with SARS-CoV-2 seronegative controls from the same population-based study with and without history of respiratory infection within 6 months prior to assessment. Primary endpoints were differences in pulmonary function, including diffusion capacity and MBW, between participants with and without evidence of SARS-CoV-2 infection. Secondary endpoints included correlation between lung function and long-lasting symptoms as well as disease severity. Findings: 73 seropositive children and adolescents (5–18 years) were recruited after an average of 2.6 months (range 0.4–6.0) following SARS-CoV-2 infection. Among 19 patients (27.1%) who complained of persistent or newly emerged symptoms since SARS-CoV-2, 8 (11.4%) reported respiratory symptoms. No significant differences were detected in frequency of abnormal pulmonary function when comparing cases with 45 controls, including 14 (31.1%) with a history of previous infection (SARS-CoV-2: 12, 16.4%; controls: 12, 27.7%; odds ratio 0.54, 95% confidence interval 0.22–1.34). Only two patients with persistent respiratory symptoms showed abnormal pulmonary function. Multivariate analysis revealed reduced forced vital capacity (p=0.012) in patients with severe SARS-CoV-2 infection. Interpretation: Pulmonary function is rarely impaired in children and adolescents after SARS-CoV-2 infection, except from those with severe infection, and did not differ between SARS-CoV-2 and other previous infections, suggesting that SARS-CoV-2 is not more likely to cause pulmonary sequelae than other infections. The discrepancy between persisting respiratory symptoms and normal pulmonary function suggests a different underlying pathology such as dysfunctional breathing.